Rekonstruksi Kriteria Kesahihan dan Penerapan Hadis Menurut Muh. Al- Gazali - Abustani Ilyas (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2008)
Muh. Al-Gazali is a Muslim scholar who is brave to make criticism towards a group of society who less accepted